Synergistic removal of Staphylococcus aureus biofilms by using a combination of phage Kayvirus rodi with the exopolysaccharide depolymerase Dpo7 - Duarte, Ana Catarina; Fernández, Lucía; Jurado, Andrea; Campelo, Ana Belén; Shen, Yang; Rodríguez, Ana; García, Pilar (Frontiers in Microbiology, 2024)
Bacteriophages have been shown to penetrate biofilms and replicate if they find suitable host cells. Therefore, these viruses appear to be a good option to tackle the biofilm problem and complement or even substitute more conventional antimicrobials. However, in order to successfully remove biofilms, in particular mature biofilms, phages may need to be administered along with other compounds. Phage-derived proteins, such as endolysins or depolymerases, offer a safer alternative to other compounds in the era of antibiotic resistance. This study demonstrates synergistic interaction between phage Kayvirus rodi with a polysaccharide depolymerase (Dpo7) from another phage (Rockefellervirus IPLA7) against biofilms formed by different Staphylococcus aureus strains. This observation was confirmed by microscopy analysis, which also showed that polysaccharide depolymerase treatment reduced, but did not eliminate extracellular matrix polysaccharides. Activity assays on mutant strains did not identify teichoic acids or PNAG/PIA as the exclusive target of Dpo7, suggesting that may be both are degraded by this enzyme. Phage adsorption to S. aureus cells was not significantly altered by incubation with Dpo7, indicating that the mechanism of the observed synergistic interaction is likely through loosening of the biofilm structure. This would allow easier access of the phage particles to their host cells and facilitate infection progression within the bacterial population.